Ralstonia solanacearum colonization of tomato roots infected by Meloidogyne incognita. Issue 6 (21st April 2019) - Furusawa, Akiko; Uehara, Taketo; Ikeda, Kentaro; Sakai, Hiroshi; Tateishi, Yasushi; Sakai, Masao; Nakaho, Kazuhiro
Abstract: Bacterial wilt, caused by Ralstonia solanacearum, is one of the most serious diseases of tomato ( Solanum lycopersicum ). Concomitant infection of R. solanacearum and root‐knot nematode Meloidogyne incognita increases the severity of bacterial wilt in tomato, but the role of this nematode in disease complexes involving bacterial pathogens is not completely elucidated. Although root wounding by root‐knot nematode infection seems to play an important role, it might not entirely explain the increased susceptibility of plants to R. solanacearum . In the present study, green fluorescent protein (GFP)‐labelled R. solanacearum distribution was observed in the root systems of the tomato cultivar Momotaro preinoculated with root‐knot nematode or mock‐inoculated with tap water. Fluorescence microscopy revealed that GFP‐labelled R. solanacearum mainly colonized root‐knot nematode galls, and little or no green fluorescence was observed in nematode‐uninfected roots. These results suggest that the gall induced by the nematode is a suitable location for the growth of R. solanacearum . Thus, it is crucial to control both R. solanacearum and root‐knot nematode in tomato production fields to reduce bacterial wilt disease incidence and effects.